PELATIHAN SENAM POCO-POCO OLAHRAGA UNTUK MENINGKATKAN KEBUGARAN JASMANI PADA SISWA SEKOLAH DASAR - Muhammad Rusli; Suhartiwi Suhartiwi; Marsuna Marsuna (Jurnal Abdi Insani, 2022)
Physical education is a goal that is carried out through physical activity that can develop human qualities in achieving goals. Exercise that is carried out regularly will improve physical fitness. Students who have fitness will have endurance and concentration in dealing with an increasing learning load. Exercise can be developed by participating in motion activities, one of which is through sports poco-poco gymnastics. the purpose of poco-poco sports activities is to provide education about poco-poco gymnastics as an effort to improve physical fitness and the cognitive, affective and psychomotor abilities of elementary school students. The method of implementing this training uses the demonstration method, while the place for this training is held at the village hall of Watumeeto, Lainea sub-district, Konawe Selatan district, Southeast Sulawesi. The training was attended by elementary school students consisting of two schools, namely SD Negeri 3 Lainea and SD Negeri 4 Lainea with a total of approximately 60 students and two accompanying teachers from each school. The implementation process lasted for 1 (one) day, which was carried out on October 1, 2022. Based on the results of the dedication of the participants who took part in the training, they were very enthusiastic and enthusiastic, students or participants were more familiar with the poco-poco sports gymnastic movements which consisted of athletic movements, football, boxing, badminton , swimming, basketball, martial arts, volleyball and weightlifting. All movements that are performed without tools but packaged in sports poco-poco movements, where this movement begins with poco-poco steps, two steps to the right and two steps to the left, with a count of 8 x 8 repetitions. So that the conclusion of this activity can produce little instructors who can guide poco-poco gymnastics in the school environment and in the community environment and participants hope that there will be more training activities related to other gymnastics training.